From autoantibody research to standardized diagnostic assays in the management of human diseases – report of the 12th Dresden Symposium on Autoantibodies. (July 2016) - Conrad, K; Andrade, L E C; Chan, E K L; Mahler, M; Meroni, P L; Pruijn, G J M; Steiner, G; Shoenfeld, Y
Testing for autoantibodies (AABs) is becoming more and more relevant, not only for diagnosing autoimmune diseases (AIDs) but also for the differentiation of defined AID subtypes with different clinical manifestations, course and prognosis as well as the very early diagnosis for adequate management in the context of personalized medicine. A major challenge to improve diagnostic accuracy is to harmonize or even standardize AAB analyses. This review presents the results of the 12th Dresden Symposium on Autoantibodies that focused on several aspects of improving autoimmune diagnostics. Topics that are addressed include the International Consensus on ANA Patterns (ICAP) and the International Autoantibody Standardization (IAS) initiatives, the optimization of diagnostic algorithms, the description and evaluation of novel disease-specific AABs as well as the development and introduction of novel assays into routine diagnostics. This review also highlights important developments of recent years, most notably the improvement in diagnosing and predicting the course of rheumatoid arthritis, systemic sclerosis, idiopathic inflammatory myopathies, and of autoimmune neurological, gastrointestinal and liver diseases; the potential diagnostic role of anti-DFS70 antibodies and tumor-associated AABs. Furthermore, some hot topics in autoimmunity regarding disease pathogenesis and management are described.